Development of a geospatial toolkit for modelling and assessment of integrated land and sea use scenarios of Boracay Island - Pagkalinawan, Homer M.
A series of geographic information system (GIS) - based tools was used to implement an ecosystem-based management (EBM) approach in modelling and assessment of integrated land and sea use scenarios in Boracay Island. Land use scenarios were created and evaluated to assess their socio-economic and environmental impacts. With the perceived interconnectivity between land and sea, marine elements and their exposure to these environmental impacts were also identified and evaluated. The results were presented to stakeholders and based on their feedback, a preferred mitigation scenario was created. Three scenarios were initially considered based on the 2013-2022 Comprehensive Land Use Plan (CLUP) of the Malay Local Government Unit (LGU) - existing land use, proposed land use and future trend land use. The amount of development and its spatial distribution in the two latter scenarios were computed using build-out analysis. To help in the visualization and presentation of each scenario, 3D models were created. Numerical models that would best reflect the socio-economic attributes of each scenario were derived from historical values and results of field survey. Socio-economic attributes e.g. population, electricity and water consumption and tourist arrival were computed for the existing land use and were deemed comparable to actual values. Values derived for the two future scenarios shows an increase ranging between 20% and 170% across the different socio-economic attributes. Environmental impacts were also identified and assessed from the land use scenarios. Exposure of terrestrial elements, particularly trees and vegetation, to different factors of environmental disturbances such as land use, distance from roads and distance from buildings were subjected to increased exposure from disturbance factors. Runoff and pollutant load modelling indicated urban flooding and nitrate and chemical oxygen demand (COD) concentration in the drainage system of the island. The model considered an extreme scenario for rainfall data such as when Typhoon Glenda brought about torrential rain in the island last July 2014. Nitrate load estimation was also carried out, utilizing results of the build-out analysis to identify location of additional sources in the two future scenarios. Increase in nitrate output were estimated at 23% and 18% for future trend land use and proposed land use scenarios, respectively. Input nutrient values were derived from field measurements while imperviousness values were based on remote sensing and land use. Lastly, exposure of marine elements to identified water disturbance factors such as water use, dive frequency per site and nitrate load output from nitrate load estimation were evaluated. Results indicated that about two-thirds of the remotely-sensed coral cover data were exposed to at least one disturbance. Findings of the study were generally well-accepted by the interviewed local stakeholders. Based on their comments and suggestions, a preferred mitigation scenario was created which entails lower density metrics and additional development constraints.